Electric vehicle adopters in Lisbon: motivation, utilization patterns and environmental impacts - Rolim, Catarina C.; Baptista, Patrícia C.; Farias, Tiago L.; Rodrigues, Óscar (European Journal of Transport and Infrastructure Research, 2014)
The introduction of alternative vehicle technologies as a response to pressure regarding fossil fuel dependency in the transportation sector poses several questions regarding their impact on travel and driving behaviour and also on the environment. This project aims to assess electric vehicle users’ motivations, daily patterns and vehicle operation and management. Promoted by EMEL – Lisbon’s mobility and parking municipal company – the project was publicized among Lisbon’s electric vehicle users, who were offered, as an incentive, a green permit which allowed them to park the vehicles for free on the street within the city’s metropolitan central area. Data were gathered over a period of one year from 25 users (private and fleet drivers) through interviews and on-board diaries, comprising a total of 5,132 trips, 49,785 km travelled and a total of 8,529 kWh charged related to 831 charges. The results indicate that environmental and economic (lower running costs) factors are the main drivers for electric vehicle adoption by private users, whereas fleet drivers mention their company’s image as the motive behind the deployment of this technology in fleets. Private users’ energy consumption and CO2 emissions were also estimated. When compared to conventional internal combustion engine vehicles running on gasoline or diesel, electric vehicles reveal considerable reductions in both energy consumption and CO2 emissions in a Well-to-Wheel life cycle approach. These decreases are between 35–43% for energy consumption and 58–63% for CO2 emissions.